Representative budgeting: women mayors and the composition of spending in local governments - Philips, Andrew Q. (2019)
One potential consequence of increasing women$1 (Bs numeric representation is that women elected officials will behave differently than their men counterparts and improve women$1 (Bs substantive representation. This study examines whether electing women to local offices changes how local government expenditures are allocated in ways that benefit women. Using compositional expenditure data from more than 5,400 Brazilian municipalities over eight years, we find significant differences in the ways men and women mayors allocate government expenditures. Our findings indicate that women mayors spend more on traditionally feminine issues, and less on traditionally masculine issues, relative to men mayors. In regard to specific policy areas, we find that women spend more on women$1 (Bs issues, including education, health care, and social assistance, and less on masculine issues, including transportation and urban development, relative to men mayors. We further find that women$1 (Bs legislative representation significantly influences the allocation of expenditures as a larger percentage of women councilors increases spending on traditionally feminine issues, as well as education, health care, and social assistance, relative to other policy issues. These findings indicate that women local elected officials improve women$1 (Bs substantive representation by allocating a larger percentage of expenditures to issues that have historically and continue to concern women in Brazil. - Reproduced.s
Keywords: Local government; Women